Rational and sustainable procedure in the design of bridges using pre-stressed concrete beams a theoretical practical method - Abel Noé Xochicale Cortés (Acta Polytechnica CTU Proceedings, 2022)
Currently there is not a direct procedure for the design of this bridge system, the procedure is still based on trial and error, there are no studies that give us both the optimum number of beams and other characteristics such as the correct thickness of the slab or its adequate strength. Keeping in mind the concept of optimization, which supports the idea of sustainability and environmentally friendly structures, we apply this concept to the design of pre-stressed concrete girder bridges, which are an integral part of the road network in most countries of the world. Knowing also that concrete is the most produced material by man and that without it, it would be difficult to understand our current world, due to its own characteristics that make it unique when it comes to sustainability, however, its production requires energy and material consumption, that is why an optimal design of a superstructure will lead to the minimum consumption of materials obtaining a more friendly design with nature. It is a global necessity to obtain and deliver concrete structures that meet the conditions of sustainability.